Evaluating the effect of corporate social responsibility communication on mobile telephone customers. (November 2016) - Chomvilailuk, Rojanasak; Butcher, Ken
Abstract: The broad aim of this study is to examine how perceived community value of a firm's corporate social responsibility initiative will affect service customer outcomes. Structural equation modelling was used with data collected from 258 telecommunication service users. Perceived community value was found to have a strong direct effect on CSR related word of mouth. While, CSR reputation had no significant direct effect on either word of mouth or switching cost. Trust mediated the influence of both independent variables on customer outcomes. Accordingly, perceived community value can assist our understanding of how CSR initiatives operate in a social media landscape.